The effective school improvement in Spain - Hechuan Sun; Miaotao Sun (Universidad Autónoma de Madrid, 2015)
The Spanish education system is currently undergoing a deep process of overall reform as a result of the gradual implementation of "the Law on the General Organization of the Education System" (LOGSE) in 1990. This deepening reform has affected the schools' general administration, autonomy, management, structure, curriculum, organization of the teaching staff and other elements (CIDE, 1996; UNESCO, 2000).